2019
DOI: 10.3390/su11041191
|View full text |Cite
|
Sign up to set email alerts
|

How Does A Firm’s Previous Social Network Position Affect Innovation? Evidence from Chinese Listed Companies

Abstract: The impact of social network position on innovation has been widely confirmed in past studies. However, research on the time-lag structure of the impact is still insufficient. Within the time window 2010 to 2017, this study constructs a two-mode social network between Chinese listed companies and other participants. To analyze the lag structure of the effect of social network position on innovation, this study uses a panel negative binomial regression model transformed by the Almon polynomial. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Then, the intensity of the network effect can improve the value utility of the mobile applications and extend the duration of innovation diffusion. In line with the research of Wei et al [3] and Muller and Peres [7], this research evidence also supports the important role of network structure in the diffusion of mobile application innovation. Our findings also emphasize the impact of the user's preferences and neighbor's influence on personal decisions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Then, the intensity of the network effect can improve the value utility of the mobile applications and extend the duration of innovation diffusion. In line with the research of Wei et al [3] and Muller and Peres [7], this research evidence also supports the important role of network structure in the diffusion of mobile application innovation. Our findings also emphasize the impact of the user's preferences and neighbor's influence on personal decisions.…”
Section: Discussionsupporting
confidence: 89%
“…Nowadays, market competition in mobile applications is increasingly fierce. The success of the mobile application in market promotion not only helps Internet enterprises to seize the market and create business value, but also allows firms establish a good reputation and gain a competitive advantage [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No scholars have analyzed whether the structure of city innovation networks will affect innovation. In addition, existing research generally believes that higher degree centrality reduces the cost of acquiring knowledge and talent for network members, so the degree centrality positively affects innovation performance [25]. However, this article concludes that there is an inverted U-shaped relationship between city centrality and green innovation efficiency, which makes up for the lack of analysis of the positive and negative effects of centrality in the existing literature.…”
Section: Discussionmentioning
confidence: 77%
“…Some researchers believe that heterogeneity in innovation performance comes from the abilities to access and create the resources [23], when using external knowledge resources to innovate, it's easy for enterprises to produce innovation without the guidance of partners if innovative resources can be fully absorbed and utilized [24]. Dong found that the acquisition of innovative resources depends on knowledge network centrality [25]. Therefore, the centrality increases the chances of acquiring innovative resources [26], the innovation network plays an important role for network members to acquire innovation resources through inter-organizational relationships, and the positions of members in the network structure directly affect their ability to acquire resource.…”
Section: Introductionmentioning
confidence: 99%